The bibliosphere doctrine is a new contribution in library-information science - G. N. Shvetsova-Vodka (Библиосфера, 2017)
The article considers the concept of the bibliosphere functions entered by A. V. Sokolov, terminology denotations and description of separate functions of librarianship, book publishing, bookselling business and bibliographic information, as well as a document and a book. The unity of essence functions of documents, books, and all social institutes of bibliosphere is established. New names of specific social functions of librarianship, book publishing and bookselling institutions are offered from positions of documentology.